Evolution of structural and optical properties of Ag implanted CrN thin films with annealing temperature - Novakovic, Mirjana; Popovic, Maja; Schmidt, E.; Schoeppe, P.; Mitric, Miodrag; Bibic, N.; Ronning, Carsten; Rakocevic, Z. (Journal of Alloys and Compounds, 2017)
This study reports on the changes of the structural and optical properties occurring in CrN thin films upon Ag ion implantation. The films were grown by reactive sputtering on top of Si (100) wafers at a temperature of around 150 °C. Subsequently, the films were implanted with Ag ion fluences in the range of 0.5 × 1016 ions/cm2 ‒ 2 × 1016 ions/cm2 with energy of 200 keV. The structural and morphological changes, promoted by in-vacuum annealing of the as-implanted thin films at 200 °C, 400 °C and 700 °C, resulted in different optical responses of the CrN:Ag films due to the formation of Ag nanoparticles. The nanoparticles were inhomogenously distributed through the layer, which is related to the implantation distribution of silver in CrN. Apart from this, Ag nanoparticles with a size of 20–25 nm were formed at the surface of the layer. These structural properties are responsible for the formation of a broad optical absorption peak. This peak is located at ∼420 nm and can be associated with the plasmon resonance of Ag particles embedded in the CrN matrix.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Ag nanoparticles; CrN films; Ion implantation; Spectroscopic ellipsometry; Surface plasmon resonance